Coordination of elbow, shoulder, and trunk movements in the backswing phase of baseball pitching to throw a fastball - Katsumata, H.; Yamamoto, M.; Kunikata, F. (International Journal of Kinesiology & Sports Science, 2022)
Background: Baseball pitchers adopt a backswing motion to accelerate a forward swing of the arm and project the ball. However, knowledge about the backswing movement for delivering a fast pitch has not been accumulated enough. Objective: This study aimed to identify the kinematic parameters of the backswing movement associated with differences in the speed of pitches and capture the joint kinematics of the throwing arm in the backswing phase. Methodology: Based on the quasi-experimental study design, fifteen male college students with various levels of baseball experience pitched a baseball at their maximum, 40%, 60%, and 80% of their full ball speed. A motion capture system sampled data at 250 Hz, and three-dimensional data were acquired for shoulder and elbow joint movements, upper-trunk rotation, and ball movement in the backswing phase. Correlation analysis between the joint and ball parameters was conducted, and the relative timings of these parameters were calculated. Results: The speed of pitch showed a significant correlation with the ball peak speed in the backswing phase (r = 0.75), which showed a significant correlation with the velocity of the elbow flexion (r = -0.81), shoulder abduction (r = 0.75), external rotation (r = -0.86) and the upper trunk`s rotation (r = 0.75). Conclusions: The backswing movement producing the higher ball`s peak speed and its abrupt transition to the forward swing was associated with the higher release speed. This kinematic feature was achieved by the temporal coordination of the arm joint movements with the upper trunk`s rotation.